Case Report: Omalizumab for Chronic Spontaneous Urticaria in Pregnancy - Liao, Shuang-Lu; Yu, Miao; Zhao, Zuo-Tao; Maurer, Marcus (Frontiers in Immunology, 2021)
Most chronic spontaneous urticaria (CSU) patients are female, and pregnancy can aggravate the disease activity of patients, but little is known about the efficacy and safety of omalizumab in pregnant CSU patients. We report two pregnant CSU patients treated with omalizumab and review the published information on omalizumab treatment during 11 pregnancies. The outcomes reported on patients with known pregnancies showed they had normal pregnancies and healthy babies as well as complete control of their CSU. The two new cases we reported support the view that omalizumab could be an effective and safe treatment option for pregnant and breastfeeding CSU patients. Further high-quality studies need to be carried out in order to obtain more information on the long-term efficacy and safety of the use of omalizumab during pregnancy in patients with chronic urticaria, including CSU.